THE IMPACT OF APPLYING INTERNATIONAL ACCOUNTING STANDARDS IN JOINT-STOCK COMPANIES LISTED ON THE IRAQI STOCK EXCHANGE - Abbas Fadel Chiyad; Murtadha Muhammad Bandar (Scholar Express Journals, 2024)
This article aims to demonstrate the need for international accounting standards that are generally accepted by practitioners of the accounting and oversight profession in all countries of the world, as a result of many changes that take place in accounting treatments in joint-stock companies operating in international financial and economic markets, including the globalization of the world economy and the growth and liberalization of trade. Globalization, direct international investment, and the development of global financial markets, in addition to the changes that occurred in the world’s monetary systems, the growing power of multinational companies, and the merger of companies and partnerships between them
Keywords: International accounting standards; financial reporting standards; accounting measurement